Situational and emotional influences on the acceptability of wolf management actions in the Greater Yellowstone Ecosystem - Jerry J. Vaske; Jennifer M. Roemer; Jonathan G. Taylor (Wildlife Society Bulletin)
Abstract Emotions play a key role in our experiences with and our responses to wildlife. We examined the effectiveness of situational and emotional variables in predicting acceptability of management actions for wolves (Canis lupus) in the Greater Yellowstone Ecosystem, USA. We advanced 3 hypotheses: 1) both situational and emotional variables will influence acceptability ratings; 2) emotions will explain the largest proportion of variance for the lethal management action; and 3) this pattern of findings will be the same for residents and visitors of the Greater Yellowstone Ecosystem. We obtained our data from a survey of residents living near Jackson, Wyoming (n = 604, response rate = 51%) and a survey of visitors to Grand Teton National Park (n = 596, response rate = 81%). We included 2 situational variables (i.e., location of encounter, wolf status) and 3 emotional variables (i.e., sympathy for ranchers, sympathy for wolves, anger about wolves) as independent variables. The dependent variables were acceptability ratings of non‐lethal and lethal management actions. Regression analyses supported all 3 hypotheses. For both groups, situational variables accounted for between 1% and 8% of the variance in acceptability of non‐lethal management actions, while emotions explained between 3% and 20%. For the lethal management action, situational variables predicted between 3% and 5% of the variance in acceptability ratings, while emotions accounted for between 41% and 49%. Although debates regarding the status of wolves are likely to continue, these findings highlight the role emotion plays in evaluating the acceptability of management actions. © 2013 The Wildlife Society.